Belowground effects of ground‐dwelling large herbivores in forest ecosystems - Ribeiro, Letícia Gonçalves [UNESP]; Melo‐Dias, Mateus [UNESP]; Saraiva, Beatriz Maria Paccas [UNESP]; Villar, Nacho [UNESP]; Galetti, Mauro [UNESP] (Wiley, 2025)
Large terrestrial mammalian herbivores (LMHs) play a critical role in ecosystems, but the effects of these species on belowground zoogeochemistry in forest ecosystems remain poorly understood. This study aimed to investigate the influence of LMHs on belowground processes in forest ecosystems. We synthesize current knowledge on how LMH species composition, physiology and feeding habits influence belowground litter and soil properties in boreal, temperate and tropical forests of the world through a systematic review. Tropical forests host the highest diversity of LMHs, but are the least studied, with most species being threatened frugivorous ruminants and non-ruminants. Temperate and boreal forests are more studied and dominated by ruminant browsers or mixed feeder species. The impact of LMHs shows high variation among forest types, but ruminants (Cervidae) tend to have negative effects on litter and soil properties in temperate and boreal forests, thereby decelerating nutrient cycling. Whereas LMHs non-ruminants (Suidae, Tapiridae and Tayassuidae) positively affect litter and soil properties in temperate and tropical forests. Research on the effects of LMHs on litter and soil properties faces several challenges, including confounding factors, such as biotic and abiotic conditions, high contextual variability influenced by factors, such as forest type, seasonality and experiment time, and there is also a geographical bias, with most studies conducted in temperate forests, while research in tropical forests remains scarce. LMHs are highly threatened by defaunation, which can disrupt ecosystem dynamics, highlighting the need to address research gaps. Long-term studies in tropical forests, particularly in South and Central America, Africa, India and Southeast Asia, are essential to understand the effects of LMHs on belowground properties. While LMHs are hypothesized to reduce nutrient cycling in forest ecosystems, this effect appears to be highly context dependent underscoring the need for further research. Understanding these effects is critical for advancing ecological knowledge and predicting climate change impacts on forest ecosystems. In addition, this can guide trophic restoration efforts and enhance ecosystem resilience.